Acquired factor V inhibitor associated with life-threatening bleeding and a mixing test result that indicated coagulation factor deficiency. (1st September 2013) - Ashizawa, Masahiro; Kimura, Shun-ichi; Wada, Hidenori; Sakamoto, Kana; Sato, Miki; Terasako, Kiriko; Kikuchi, Misato; Nakasone, Hideki; Okuda, Shinya; Kako, Shinichi; Yamazaki, Rie; Oshima, Kumi; et al.
Abstract : A mixing test is useful for distinguishing between coagulation factor deficiency and the presence of inhibitor as the cause of coagulopathy. However, we experienced a patient with acquired factor V (FV) inhibitor whose mixing test showed a coagulation factor deficiency pattern. A 65-year-old man with a tendency for bleeding was referred to our center. The laboratory data showed remarkable prolongation of prothrombin time and activated partial thromboplastin time (APTT). FV activity was less than 3%. A mixing test showed a coagulation factor deficiency pattern. However, neither the tendency for bleeding nor the coagulation tests were corrected by transfusion of fresh frozen plasma. A few days later, a positive test for FV inhibitor of 3 Bethesda units was obtained. Therefore, we started prednisolone and plasma exchange, and the coagulation test results normalized after 6 weeks. Although an incubation period is generally not considered necessary in a mixing test for FV inhibitor, we repeated mixing tests with various incubation periods and confirmed an incubation period-dependent prolongation of the APTT. Therefore, a mixing test with an incubation period is recommended for the detection of FV inhibitor, since a mixing test without an incubation period may show a coagulation factor deficiency pattern when the titer of FV inhibitor is low.